Six cases of acute hepatitis type B with arthritis as the initial symptom - NAGAOKA, Kengo; FUKUDA, Yoshihiho; TAKECHI, Hajime; UENO, Masao; KOKURYU, Hiroyuki; SAKAI, Yuuji; IMURA, Hiroo; KOHIGASHI, Katsuji; HIRAIWA, Nozomu; NAKABOU, Yukiharu; SEKO, Shuuji; HIMENO, Yasuo; et al. (Kanzo, 1988)
We present six patients with severe joint pain who were found to have hepatitis B virus (HBV) infection and the pathogenesis is discussed in this paper. The sera from five patients in the acute phase of their joint symptoms were obtained, so we determined the circulating immune complexes (IC) which had been thought to be the pathogenesis of arthritis. IC were detected in 2 out of 5 patients (40%) by using C1q solid phase enzyme immunoassay but were not detected in all patients by Raji cell enzyme immunoassay. Alternatively, HBs antigen·antibody IC by polyethleneglycol-trypsinization method were detected in 4 out 5 patients (80%). The levels of C3 and C4 were depressed in 2 (40%) and 3 patients (60%) respectively. These results suggest that circulating IC may not be related closely to arthritis occuring in prodrome of acute hepatitis type B. Therefore, it is also important to investigate the local deposition of IC or HBV replication in joints as one of the extrahepatic menifestations.